Long-term response in patient with recurrent oropharyngeal carcinoma treated with cetuximab, docetaxel and cisplatin (TPEx) as first-line treatment followed by cetuximab maintenance. (May 2017) - Guigay, J.; Even, C.; Mayache-Badis, L.; Debbah, M.; Saada-Bouzid, E.; Tao, Y.; Deschamps, F.; Janot, F.; Lezghed, N.; Michel, C.
Abstract: Background: Cetuximab, an anti-EGFR monoclonal antibody in combination with platinum and 5FU is the standard of care in first-line treatment of patients with recurrent head and neck squamous cell carcinoma (HNSCC), with an expected median outcome of 10 months. For this population, development of efficacious and safer therapies is still needed. Case report: A 62–year-old male with a first recurrence of human papillomavirus positive stage IVA (T3N2bM0) adenocarcinoma of the glossotonsillar sulcus not amenable to locoregional curative treatment was offered chemotherapy as part of the TPEx clinical trial. He was treated by cetuximab (loading dose 400 mg/m 2 on day 1 cycle 1, then 250 mg/m 2 weekly), and chemotherapy (cisplatin 75 mg/m 2 and docetaxel 75 mg/m 2, on day 1). Cycles were repeated every 21 days for 4 cycles (TPEx regimen) with systematic granulocyte colony-stimulating factor support at each cycle. Bi-monthly maintenance cetuximab 500 mg/m 2 was then administered. The patient showed a clinical complete response according to RECIST 1.1 criteria after 5 months maintenance, with progression-free survival of 25 months. Relapses that followed were treated with stereotactic irradiation, radiofrequency ablation, cetuximab and paclitaxel. The patient is alive eleven years after cancer diagnosis and remains controlled for his disease, with a cumulative period of 59 months of cetuximab administration (equivalence of 121 injections). Conclusion: This case report demonstrated that TPEx regimen, by synergistic interaction between taxanes and cetuximab, followed by bimonthly cetuximab maintenance may lead to patient complete remission within the first year of treatment. Furthermore, prolonged intermittent treatment with cetuximab seems to participate in the improved survival associated with preserved quality of life. Key favorable prognostic factors may be moderate tumor differentiation, oropharyngeal location, HPV p16 positive tumor status.